Pengaruh Store Atmosphere, Pelayanan, Dan Lokasi Terhadap Keputusan Pembelian Kopi Nako Summarecon Bekasi - Halimah, Siti; Untari, Dhian Tyas; Rohaeni, Heni (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the influence of store atmosphere, service, and location on consumers’ purchasing decisions at Kopi Nako Summarecon Bekasi. A quantitative approach with a descriptive method was used. The sampling technique applied was accidental sampling with a total of 100 respondents. Data were analyzed using multiple linear regression through SPSS version 26. The results showed that store atmosphere had a significant effect on purchasing decisions with a significance value of 0.012. Service also had a significant influence with a significance value of 0.001, and location had a significant effect with a significance value of 0.002. Simultaneously, the three variables significantly influenced purchasing decisions with a significance value of 0.000. The coefficient of determination (R²) was 0.407, indicating that store atmosphere, service, and location collectively explained 40.7% of the variation in purchasing decisions.